DIFFERENTIATED INSTRUCTION: BENEFITS AND CLASSROOM PRACTICES IN ENGLISH CLASS - Fowen, Eric; Manda Negara, Irma (LPPM STBA Pontianak, 2024)
This study aims to describe the benefits and implementation of Differentiated Instruction by teachers in English classes. Qualitative methods are used to extract information from sources. Data was collected using interviews which consisted of several questions referring to indicators from the theory used. Then, Data analysis is carried out in three ways, including organizing and categorizing data, compiling the context of information that has been obtained, and abstracting key ideas that have been expressed. As a result, teachers implement Differentiated Instruction according to the curriculum and student needs. Students are divided into three types according to differences in students abilities, and teachers provide different treatment according to students' abilities. Then, an assessment will be carried out using observations based on student performance. Meanwhile, the benefits of DI can accommodate student needs and be more effective in involving students in the learning process. Students can get a fair opportunity from the teacher based on the level of ability obtained from the pre-assessment for learning objectives to be achieved. It is feasible to apply DI in the teaching and learning process for educators. Teachers can quickly ascertain the learning capabilities and preferred learning styles of their students.